A Case Discussion on Market‐Based Extended Producer Responsibility: The Minnesota Electronics Recycling Act. (25th January 2018) - Alev, Işıl; Huang, Ximin (Natalie); Atasu, Atalay; Toktay, L. Beril
Summary: In this article, we analyze the Minnesota Electronics Recycling Act to explore the benefits and potential drawbacks of a market‐based extended producer responsibility (EPR) legislation implementation with operational flexibility for manufacturers. Based on publicly available reports and stakeholder interviews, we find that the Minnesota Act attains two key goals of market‐based EPR (i.e., higher cost efficiencies and substantial landfill diversion); however, this may come at the expense of selective collection and recycling, an increased burden on local governments, and a loss of balance in contractual power between stakeholders. We observe that these concerns arise because of specific flexibility provisions afforded to manufacturers that allow them to operationalize their EPR compliance with a cost‐efficiency focus. Thus, we conclude that EPR goals must be carefully translated into operating rules in order to achieve goals while avoiding unintended consequences.